Kriteria Keshahihan Hadis Perpektif Syiah - Muhamad Nasir (LPPM IAIN Sultan Amai Gorontalo, 2014)
This study focused on the validity of hadith in the view of Shia, which during this portion of the discussion of hadith more in Sunni view. It is important to be studied further to enrich the scientific insights in the field of hadith that is not rigid in the face of difference. In view of Shia the hadith transmission is restricted on a track history of ahl al-bait or priest Ma'shum, and this criterion is one of the requirements for an authentic hadith assessed from the aspect sanad. In the aspect of honor, the validity of tradition criteria not mentioned explicitly by the Shiites, they just make the benchmark validity honor on the basis of conformity with the Qur'an, and not in conflict with the other authentic tradition.